2018
DOI: 10.29333/ejmste/85499
|View full text |Cite
|
Sign up to set email alerts
|

Developing Strategies to Prevent “Cyber-Bullying”

Abstract: The aim of this research was to define secondary education directors and teachers awareness of preventing "cyber-bullying". The participants are directors and teachers at Near East College in the second half of the 2016-2017 academic year. A qualitative research method was used in this study. An open-ended questionnaire was administered to obtain the participants' views. The data obtained showed that the directors and teachers were aware of "cyber-bullying" and the students faced "cyberbullying" from time to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Based on former studies (Cooper & Nickerson, 2013;Giménez-Gualdo, 2015;Ozansoy, Altınay, & Altınay, 2018), we expected to find significant differences for our last research objective: use of coping strategies to face cyberbullying. Unlike the results of Ozansoy et al (2018), which indicated that schools tended to favour technical strategies, both the teachers and families in our sample perceived three of the four presented proactive strategies as the most suitable ones, which were tell a teacher, tell a family member and seek help in the social network group, which were the most suitable ones according to Caba and López (2013) and Giménez-Gualdo (2015), but avoided technical-type strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Based on former studies (Cooper & Nickerson, 2013;Giménez-Gualdo, 2015;Ozansoy, Altınay, & Altınay, 2018), we expected to find significant differences for our last research objective: use of coping strategies to face cyberbullying. Unlike the results of Ozansoy et al (2018), which indicated that schools tended to favour technical strategies, both the teachers and families in our sample perceived three of the four presented proactive strategies as the most suitable ones, which were tell a teacher, tell a family member and seek help in the social network group, which were the most suitable ones according to Caba and López (2013) and Giménez-Gualdo (2015), but avoided technical-type strategies.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may not be the permanent solution in this era because banning on advance technology can create complexity. So, it is also important to aware and arm the parents along with teachers and friends about the knowledge and skills in eradicating bullying involvement (Chen & Zhu, 2022;Ozansoy et al, 2018).…”
Section: Strategies To Cope With Cyberbullying Through Facebookmentioning
confidence: 99%
“…Knowing how to deal with cyberbullying has also been a focus of recent research, which has revealed imprecise results specifically concerning the type of strategies perceived by teachers as effective for students to deal with cyberbullying. It remains unclear which strategies they are more inclined to favor, such as more technical strategies (e.g., changing email and passwords) or strategies focusing on seeking help and/or reporting the incident (e.g., telling a family member) (Bautista Alcaine & Vicente Sánchez, 2020; Ozansoy et al, 2018). Moreover, a systematic review about teachers’ perceptions and responses towards cyberbullying (Macaulay et al, 2018) concluded that, teachers generally considered cyberbullying as a school problem, but their knowledge about effective strategies was inconsistent, and they did not believe in their ability to identify and deal with the phenomenon.…”
Section: How Teachers Define and Deal With Cyberbullying And Their Mo...mentioning
confidence: 99%